2021
DOI: 10.1371/journal.pgen.1009807
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeler Chd1 supports MRX and Exo1 functions in resection of DNA double-strand breaks

Abstract: Repair of DNA double-strand breaks (DSBs) by homologous recombination (HR) requires that the 5’-terminated DNA strands are resected to generate single-stranded DNA overhangs. This process is initiated by a short-range resection catalyzed by the MRX (Mre11-Rad50-Xrs2) complex, which is followed by a long-range step involving the nuclease Exo1 or Dna2. Here we show that the Saccharomyces cerevisiae ATP-dependent chromatin-remodeling protein Chd1 participates in both short- and long-range resection by promoting M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Interestingly, Chd1 , a member of the Chd1 - Chd2 subfamily, has been found to reduce histone occupancy near the DSB ends and promotes DSB repair by homologous recombination. 39 , 40 The protein domains of CHD2 and CHD1 are similar. We hypothesized that CHD2, like CHD1, may promote homologous recombination repair by increasing chromatin accessibility.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Chd1 , a member of the Chd1 - Chd2 subfamily, has been found to reduce histone occupancy near the DSB ends and promotes DSB repair by homologous recombination. 39 , 40 The protein domains of CHD2 and CHD1 are similar. We hypothesized that CHD2, like CHD1, may promote homologous recombination repair by increasing chromatin accessibility.…”
Section: Resultsmentioning
confidence: 99%
“…One of these remodelers is the evolutionarily conserved Chd1 protein, whose remodeling activity is stimulated by H2B ubiquitylation in vitro [ 133 ]. Interestingly, it has recently been demonstrated that Chd1 stimulates HR and enhances both short- and long-range resection by promoting the association of MRX and Exo1 to the DSB ends [ 134 ]. Since Chd1 couples ATP hydrolysis with the reduction of histone occupancy near the DSB ends and all Chd1 functions in the DSB response require its ATPase activity, Chd1 has been proposed to facilitate MRX and Exo1 processing activities by opening the chromatin structure around the DSB [ 134 ].…”
Section: Ubiquitylation Of Histones H2a H2b and H1mentioning
confidence: 99%
“…Interestingly, it has recently been demonstrated that Chd1 stimulates HR and enhances both short- and long-range resection by promoting the association of MRX and Exo1 to the DSB ends [ 134 ]. Since Chd1 couples ATP hydrolysis with the reduction of histone occupancy near the DSB ends and all Chd1 functions in the DSB response require its ATPase activity, Chd1 has been proposed to facilitate MRX and Exo1 processing activities by opening the chromatin structure around the DSB [ 134 ]. Altogether, these findings suggest that H2B ubiquitylation contributes to regulate HR both by favoring Rad51 nucleofilament formation and by modulating resection progression, in association with other histone PTMs and chromatin remodeling enzyme activities ( Figure 5 ).…”
Section: Ubiquitylation Of Histones H2a H2b and H1mentioning
confidence: 99%
“…Eukaryotes express several nucleosome remodelers ( Flaus et al, 2006 ) and chromatin immunoprecipitation (ChIP) and related techniques have localized several of them to DSBs ( Bantele et al, 2017 ; Bennett and Peterson, 2015 ; Bennett et al, 2013 ; Bird et al, 2002 ; Chai et al, 2005 ; Chen et al, 2012 ; Costelloe et al, 2012 ; Downs et al, 2004 ; Eapen et al, 2012 ; Gnugnoli et al, 2021 ; Lademann et al, 2017 ; Morrison et al, 2004 ; Shim et al, 2005 ; 2007 ; Tsukuda et al, 2005 ; van Attikum et al, 2004 ; 2007 ). This raises the question, whether these remodelers have distinct functions at DSBs or whether they act redundantly.…”
Section: Remodelers Have Distinct Roles In Chromatin Organizationmentioning
confidence: 99%
“…Interestingly, several studies in both yeast and human cells, point towards a function of these specific remodelers in promoting homologous recombination ( Lan et al, 2010 ; Nakamura et al, 2011 ; Smeenk et al, 2012 ; Toiber et al, 2013 ; Kari et al, 2016 ; Zhou et al, 2018 ; Rother et al, 2020 ; Casari et al, 2021 ; Gnugnoli et al, 2021 ). In particular, remodelers of ISWI, CHD1 and CHD7 sub-families appear to be recruited to sites of DNA damage and to stimulate resection ( Smeenk et al, 2012 ; Toiber et al, 2013 ; Kari et al, 2016 ; Delamarre et al, 2020 ; Rother et al, 2020 ; Gnugnoli et al, 2021 ). The precise mechanism by which these remodelers promote resection and HR is however uncertain.…”
Section: The Role Of Nucleosome Positioning At Double Strand Breaks Remains To Be Determinedmentioning
confidence: 99%